The venomous coral snakes (genus Micrurus) of Costa Rica - Savage, Jay M.; Vial, James L. (Revista de Biología Tropical, 1973)
Four species of venomous coral snakes (Micrurus) occur in Costa Rica. The single bicolor species, M. mipartitus has previously been defined as two subspecies; however, variations in diagnostic characters clemonstrate dinal shift that precludes recognition of geographic races. Presence of the tricolor M. clarki is concluded from but a single Costa Rican specimen, although the species is otherwise definitely known from adjacent areas in Panamá. Variation among tricolor coral snakes allied to M. nigrocinctus suggests the presence of three populations that occupy southwestern Pacific Costa Rica, northwestern Pacific Costa Rica and western Nicaragua, and Atlantic lowland Costa Rica. Gradual intergradation in the Pacific lowlanels, as well as more complex intergrading patterns in the Meseta Central and Arenal regions and over a broad arca of Nicaragua, eliminate the value of subspecific designations. Where M. nigrocinctus occurs sympatrically with populations of the closely related M. alleni, they can be constently distinguished by differences in head cap patterns and segmental counts. Micrurus alleni is composed of three allopatric populations in the Atlantic lowlands of Costa Rica anel Nicaragua, the southwestern Pacific lowlands of Costa Rica and adjacent southwestern Panama, and Pacific lowland Darién in eastern Panama. Becaust of limited information on variation among these populations we prefer not to apply the trinomials.